2019
DOI: 10.1111/1759-7714.13055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of subsequent docetaxel +/− ramucirumab and S‐1 after nivolumab for patients with advanced non‐small cell lung cancer

Abstract: Background Cytotoxic chemotherapy for advanced non‐small cell lung cancer (NSCLC) as second‐line or subsequent treatment generally results in a poor treatment outcome. Several reports have indicated that subsequent cytotoxic chemotherapy in patients who have received immune checkpoint inhibitors (ICIs) might have relatively better efficacy. Methods The clinical data of advanced NSCLC patients treated with nivolumab during clinical practice at the National Cancer Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Tamura et al also indicated that the effectiveness of docetaxel with or without Figure 1. ramucirumab or S1 therapy after nivolumab might be enhanced (5,8), and our results are consistent with their findings.…”
Section: Discussionsupporting
confidence: 93%
“…Tamura et al also indicated that the effectiveness of docetaxel with or without Figure 1. ramucirumab or S1 therapy after nivolumab might be enhanced (5,8), and our results are consistent with their findings.…”
Section: Discussionsupporting
confidence: 93%
“…DTX or DTX + RAM was also recently reported to achieve a higher response rate as a subsequent chemotherapy after nivolumab compared to that without prior nivolumab treatment [18,19]. In this study, DTX + RAM showed a preferable response rate in ORR among the common regimens.…”
Section: Effectivenessmentioning
confidence: 49%
“…Previous reports on S-1 monotherapy have been compared with the findings of this study (Table 3). 2,8,9,[12][13][14][15][16][17][18][19] Interestingly, in two studies on efficacy of S-1 with a registration period prior to 2009, S-1 showed higher ORR in adenocarcinoma or non-SQ than in squamous cell carcinoma. 13,14 PEM was probably not administered to the analyzed populations because the efficacy of PEM was not improved in clinical trials at the time.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unknown whether ICIs improve the treatment efficacy of S-1. 18,19 Exploratory analysis on the predictive factor of S-1 after PEM suggested a longer period between last PEM administration and first S-1 administration. It might therefore be an option to avoid S-1 treatment immediately after PEM.…”
Section: Discussionmentioning
confidence: 99%